2016
DOI: 10.1371/journal.pone.0166700
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant IgA1 Glycosylation in IgA Nephropathy: A Systematic Review

Abstract: ObjectiveGalactose-deficient IgA1 was evaluated in patients with IgA nephropathy(IgAN) and controls in order to determine the predictive value of galactose-deficient IgA1 in cases of IgA nephropathy.MethodsPubMed, EMBASE, Cochrane central register of controlled trials, CNKI, CBM disc, and VIP database were searched to identify eligible studies that evaluated a difference in aberrant IgA1 glycosylation in IgAN patients compared with controls. A meta-analysis was conducted to evaluate the impact of galactose-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
5
26
2
Order By: Relevance
“…It found no significant differences in the level of serum Gd-IgA1 between IgAN patients and their first-degree relatives. However, the level of serum Gd-IgA1 was found significantly higher in IgAN patients than in healthy controls or patients with other renal diseases, but the level of serum Gd-IgA1 was not associated with the disease severity [51].…”
Section: Increased Production Of Galactose-deficient Iga1 (Gd-iga1)mentioning
confidence: 68%
“…It found no significant differences in the level of serum Gd-IgA1 between IgAN patients and their first-degree relatives. However, the level of serum Gd-IgA1 was found significantly higher in IgAN patients than in healthy controls or patients with other renal diseases, but the level of serum Gd-IgA1 was not associated with the disease severity [51].…”
Section: Increased Production Of Galactose-deficient Iga1 (Gd-iga1)mentioning
confidence: 68%
“…At present, these conditions have not been yet identified. Experimental evidence indicates that only degalactosylated IgA is able to activate the MBL pathway (10)(11)(12). This raises the hypothesis that both MBL deposits and activation of the complement via this pathway (and the ensuing C4d deposits) could be related to the degree of IgA1 glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…The current working model for the pathogenesis of IgAN indicates that, after mesangial deposition of galactose-deficient IgA1, IgA1/IgG, or IgA/IgA immune complexes, these deposits (via interaction with specific mesangial receptors or via direct activation of complement) induce activation, proliferation, increased mesangial matrix synthesis, and eventually, cell injury. Several studies have shown that mesangial IgA deposits can activate complement via two pathways that are not mutually exclusive (1,(8)(9)(10). In the majority of patients, the presence of mesangial IgA deposits colocalizes with C3 but not with IgG or C1q deposits, suggesting that activation occurs through the alternative pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, IgAN is characterized by mesangial cell proliferation with IgA-IC deposition in the glomerular mesangium, which is indistinguishable from pathologic findings of HSPN [2,12,14]. Regarding the pathogenesis of IgAN, several studies that investigated aberrant IgA1 O-glycosylation indicated that galactose-deficient IgA1 (Gd-IgA1) plays a pivotal role in the progression of IgAN [15][16][17][18][19][20][21][22][23]. According to these studies, patients with IgAN have aberrant IgA1 molecules with a Gal deficiency of O-linked glycans in the hinge region, which indicates that Gd-IgA1 consists of terminal N-acetyl-galactosamine (GalNAc) or sialylated GalNAc [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%